2020
DOI: 10.3390/en13010215
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Construction Duration and Schedule Robustness Based on Hybrid Grey Wolf Optimizer with Sine Cosine Algorithm

Abstract: Construction duration and schedule robustness are of great importance to ensure efficient construction. However, the current literature has neglected the importance of schedule robustness. Relatively little attention has been paid to schedule robustness via deviation of an activity’s starting time, which does not consider schedule robustness via structural deviation caused by the logical relationships among activities. This leads to a possibility of deviation between the planned schedule and the actual situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Given the above analysis, it can be concluded that GWO, the NBA, and the WOA can find the best solutions, and there is no statistically significant difference between the quality of their solutions. Given the relatively new advent of these three metaheuristics (i.e., GWO, NBA, and WOA), few studies have reported their efficiency in the solution of different construction planning problems such as the optimization of construction duration and schedule robustness using GWO [126], and the construction stage and zone optimization of Rockfill dams using the WOA [127]. On the other hand, the FA generates less optimal solutions than those produced by the others, while the SSA provides the worst results.…”
Section: Statistical Results Of the Si Metaheuristicsmentioning
confidence: 99%
“…Given the above analysis, it can be concluded that GWO, the NBA, and the WOA can find the best solutions, and there is no statistically significant difference between the quality of their solutions. Given the relatively new advent of these three metaheuristics (i.e., GWO, NBA, and WOA), few studies have reported their efficiency in the solution of different construction planning problems such as the optimization of construction duration and schedule robustness using GWO [126], and the construction stage and zone optimization of Rockfill dams using the WOA [127]. On the other hand, the FA generates less optimal solutions than those produced by the others, while the SSA provides the worst results.…”
Section: Statistical Results Of the Si Metaheuristicsmentioning
confidence: 99%
“…Construction duration T and schedule robustness, which is measured using the composite robustness criterion using the weighting methods proposed in this paper and the traditional weighting methods, respectively, are the two optimization objectives. A hybrid grey wolf optimizer with a sine-cosine algorithm is adopted to solve the optimization model [50]. The iteration number is set as 1000.…”
Section: Comparison Of Weighting Methodsmentioning
confidence: 99%
“…To explain the influence of weather conditions on the simulation activity precedence logic and the role of construction activity sequence classification in simulations, a criterion denoted as the structural deviation (SD) is adopted to describe the consistency between the simulation activity logic relationship and the actual situation (Zhao et al, 2020). SD is the absolute value of the weighted summation of the deviations between the actual and simulation activities during each simulation cycle: SD=false∑i=0nwi||Pigoodbreak−pi where P i denotes the sequence of the actual construction activities, p i denotes the simulation activity sequence and w i denotes the time of the i‐ th activity as a percentage of the total cycle time.…”
Section: Case Studymentioning
confidence: 99%